Seasonal dynamics and molecular regulation of flavonoid biosynthesis in Cyclocarya paliurus (Batal.) Iljinsk - Chen, Duo; Xiao, Yixin; Zheng, Xuehai; Sun, Huamiao; Zhang, Cifeng; Zhu, Jinmao; Xue, Ting (Frontiers in Plant Science, 2025)
IntroductionCyclocarya paliurus, an economically important species known for its high flavonoid content, has potential for industrial applications. Understanding the seasonal dynamics and molecular regulation of flavonoid biosynthesis in this species is crucial for optimizing its production.MethodsWe conducted an integrated analysis of transcriptomic and metabolomic data to identify key genes involved in flavonoid biosynthesis and regulation. Seasonal variation in flavonoid content and gene expression was examined, with a focus on the genes involved in the flavonoid synthesis pathway and their correlation with flavonoid levels. ResultsFlavonoid content peaked in August and declined towards November, with quercetin and kaempferol glycosides being the most abundant compounds. Pearson correlation analysis revealed significant relationships between the functional genes of the flavonoid synthesis pathway and flavonoid content. Seasonal variations in the expression of key biosynthetic genes (CHS, CHI, F3H, DFR, FLS) and regulatory transcription factors (MYB11, MYB12, MYB111, MYB75, MYB90, bHLH, WD40) were strongly correlated with flavonoid levels, particularly under environmental stress.DiscussionThese findings provide insights into the genetic regulation of flavonoid biosynthesis in C. paliurus and highlight the importance of seasonal and environmental factors. This knowledge has practical implications for industrial breeding and biotechnological applications, particularly in enhancing the functional properties of C. paliurus for industrial use. Our study establishes a foundation for future research aimed at optimizing flavonoid production in this species and exploring its potential for bioactive compound production.